Renewable Energy Production and Storage Options and their Economic Impacts in Hungary - Németh, Márton (Public Finance Quarterly, 2022)
The study reviews the most relevant renewable energy sources, focusing on their possible application, economic aspects and potential for Hungary. Feasibility and economic analysis is made for plant-sized photovoltaic devices, wind turbines, geothermal power plants and biomass power plants. It was found that solar cell technology has the highest revenue. However, its further spread is limited by several factors, such as the reactive effect on the energy market, grid problems, and weather dependency. A possible solution for these problems is to use energy storage systems. For the sake of simplicity, only the economically mature technologies are investigated, including pumped hydroelectric storage, batteries, green hydrogen production, and thermal energy storage connected to a heat power plant. The payback calculations require a simple simulation algorithm to calculate the revenue using Hungarian data. With the simulation, the most important economic indicators are estimated. As a result of these calculations, we suggest a pumped hydroelectric storage to be built, or if it is impossible, the Paks 2 nuclear plant should be completed with a thermal energy storage facility.